(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2016)
Tethyan calcareous nannofossil assemblages have been recorded from three sections of the Abtalkh Formation including the type section at Abtalkh village and two others (Padeha and Jalilabad) in the east Koppeh-Dagh Basin, north east of Iran. The formation studied is expanded with a thickness of up to 1770 m at the type locality in the middle of eastern Koppeh-Dagh spanning biozones UC15bTP to UC16 while in the Padeha (973.5 m thick) in east and Jalilabad (1316 m thick) section in the west the formation spans biozones UC14dTP–UC15aTP to of UC16. The zonation erected indicates an age of early–latest Campanian for the Abtalkh Formation. The recorded assemblages are of low-latitude to intermediate forms suggesting placement of the Koppeh-Dagh Basin in low to intermediate latitudes during Campanian.